Metal Decoration and Magnetic Field Effect on the Electrical Breakdown Voltage for ZnO Nanorods Gas Ionization Sensor - Liu, Chunming; Zheng, Zhi; Chen, Jiajun; Su, Haiqiao; Xiang, Xia; Zu, Xiaotao; Zhou, Weilie (Frontiers in Materials, 2019)
ZnO nanorod arrays with sharp tips were synthesized via chemical vapor deposition and utilized as the anode for gas ionization sensor. The effects of metal (Mn, Ni81Fe19 and Au) decoration and magnetic field on the electrical breakdown voltage were studied. Compared with the bare ZnO nanorod, metal decorated ZnO nanorod arrays in the magnetic field can effectively reduce the breakdown voltage for the air to 20 V. The possible mechanism is that metal decoration produces small size protuberance on the surface of ZnO nanorods and then enhances the electrical field near the tips. The magnetic field exerts action on the motion of the electron and therefore increases electron impact ionization efficiency and second electron emission efficiency.